Perubahan Sosial Budaya Masyarakat di Desa Wisata Karangbanjar Kabupaten Purbalingga (Solidarity: Journal of Education, Society and Culture, 2014)
This research aims to study the social behavior of society culture in Karangbanjar tourism village, Sub-Province of Purbalingga. Research method which is used in this research is qualitative research method. Technique of data collection is using observation, interview, and documentation collecting technique. The validity of data research using triangulation of data technique. Data analysis in this research use interactive analysis models with data collecting phase: data reduction, data presentation, and conclusion or verification. The result of this research indicate that Karangbanjar village formed to became a tourism village is the reason of the behavioral changing of Karangbanjar resident’s cultural social. The Sub-Province of Purbalingga have many kind of tourism object which is influenced in the economic development, one of them is Tourism Village. Karangbanjar village chosen to become the Tourism Village is because of this village own a lot of potential matter which is supporting the succeed of Tourism Village including natural potencial, economic potencial and cultural potencial. The forming of Karangbanjar Village to became a Tourism Village give a significant changes perceived by Karangbanjar village society including social behavioral changes, cultural and economics behavioral of Karangbanjar torism village society.